Public Speaking Anxiety and English Language Competency of Bachelor of Secondary Education English Majors - Ma Fe B Reyes; Dialyn Samson; Carol A Tamayo; Jomari P Valeña; Maria Teresa M Rodriguez (Journal of Elementary and Secondary School, 2023)
This research aimed to determine the public speaking anxiety and English language competency of the Bachelor of Secondary Education English majors at Laguna State Polytechnic University Los Baños Campus. The study employed a descriptive correlation research design using a validated survey questionnaire to find the relationship between the variables. In the study's findings, the respondents' public speaking anxiety level had a standard deviation of 0.71 and was descriptively interpreted as "agree". The level of English language competency of the students was proficient. The data showed that 70.5% of the respondents have proficient English Language competency while 22.7% were advanced, and 6.8% were approaching. Thus, the study shows no significant relationship between public speaking anxiety and English Language Competency. Based on the results, it is suggested that respondents should enhance their skills in public speaking though it did not affect their language proficiency. Implementing activities that would practice and develop the student's speaking skills is encouraged to future educators to prevent anxiety towards speaking. Since the students' PSA level is high, teachers need to guide the students with their speaking, their delivery and confidence along the process.